2015
DOI: 10.1259/bjr.20150159
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose CT screening using hybrid iterative reconstruction: confidence ratings of diagnoses of simulated lesions other than lung cancer

Abstract: Objective: To evaluate the confidence ratings of diagnoses of simulated lesions other than lung cancer on low-dose screening CT with hybrid iterative reconstruction (IR). Methods: Simulated lesions (emphysema, mediastinal masses and interstitial pneumonia) in a chest phantom were scanned by a 320-row area detector CT. The scans were performed by 64-row and 160-row helical scans at various dose levels and were reconstructed by filtered back projection (FBP) and IR. Emphysema, honeycombing and reticular opacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
2
1
Order By: Relevance
“…Interestingly, Iodixanol demonstrated superior CNR levels compared to Iohexol at 200 and 400 mAs where no difference between both ICM was noted at 350 mAs. Previous studies have demonstrated that IR application provides a reduction in image noise and an increase in CNR compared to FBP [25][26][27][28]. In our study, no significant difference in image noise and phantom opacification was noted when employing FBP, MBIR and MBIR.…”
Section: Discussioncontrasting
confidence: 48%
“…Interestingly, Iodixanol demonstrated superior CNR levels compared to Iohexol at 200 and 400 mAs where no difference between both ICM was noted at 350 mAs. Previous studies have demonstrated that IR application provides a reduction in image noise and an increase in CNR compared to FBP [25][26][27][28]. In our study, no significant difference in image noise and phantom opacification was noted when employing FBP, MBIR and MBIR.…”
Section: Discussioncontrasting
confidence: 48%
“…Sakai et al used simulated GGO and reticular Conventional CT chest protocol in the same patient would result in DLP of 264.55 mGy × cm and CTDIvol of 5.92 mGy, which means that low-dose protocol decreased the radiation dose to about 50% without a significant impact on the diagnostic value. (CT protocol: 100 kVp, 50 mAs, 0.5 s without iterative reconstruction) opacity lesions and implemented them inside the apex and lower lobe of the lung [30]. They obtained LDCT images using the IR method in various levels of radiation dose and compared it with filtered back projection (FBP) method which is widely used in scanners.…”
Section: Low-and Ultra-low-dose Ct Scan Protocolmentioning
confidence: 99%
“…Several studies have demonstrated that IR techniques help improve image quality and retain diagnostic value of LDCT at substantially reduced radiation dose [6][7][8].…”
Section: Low-dose Ct For Lung Cancer Screeningmentioning
confidence: 99%